MODERN DIGITAL TECHNOLOGIES IN TEACHING DIGITAL PAINTING - Zaluzhna, Halyna; Nefodova, Inna; Zubenko, Svitlana (Theory and practice of design, 2025)
The purpose. To investigate the impact of digital technologies on the educational process in the field of digital painting. Methodology. Analytical, socio-cultural, structural approaches, as well as theoretical research methods were applied. Results. The key features of digital painting as a modern direction of fine art, which is integrated into the system of professional art education, have been identified. It has been found that digital painting requires not only technical skills in mastering software tools, but also a new type of artistic thinking capable of combining creativity with technology. It has been established that the effectiveness of the educational process increases significantly when students work on topics that are personally significant or socially relevant for them. This contributes to a deeper involvement in creativity and the formation of an author’s style. Scientific novelty. A comprehensive understanding of digital painting as a specific direction of fine art in the context of modern art education has been carried out. A systematic approach to the methodology of teaching digital painting has been proposed, taking into account digital tools, forms and teaching methods. The key components of an effective educational process in the field of digital art, based on the integration of technological innovations and artistic and aesthetic principles, have been identified. Practical relevance. The results of the study can be used by teachers of art education institutions to update curricula, create modern courses in digital painting, and implement innovative teaching methods.